Hubungan Tingkat Pendidikan dengan Kecemasan Pasien Pre Operasi dengan Spinal Anestesi - Muh Hafiduddin; Atiqah Zahira (Vitamin : Jurnal ilmu Kesehatan Umum, 2025)
This study is based on the phenomenon of anxiety that patients almost always experience before undergoing surgery, which generally arises due to limited information regarding the upcoming medical procedure. Anxiety is understood as a psychological response closely related to stress and can be influenced by various factors, including the patient's education level. Education plays a crucial role in increasing a person's general knowledge, particularly in understanding medical theories, procedures, and risks, thus enabling patients to make better decisions and reducing anxiety. In the context of spinal anesthesia, knowledge about the preparation, procedure, and side effects of anesthesia can help patients feel more mentally prepared. The main objective of this study was to analyze the relationship between education level and anxiety levels in patients undergoing spinal anesthesia. This study used a quantitative approach with a cross-sectional correlation design and involved 49 respondents selected through a purposive sampling technique. The data collection instrument used the APAIS questionnaire, while data analysis was performed using the Spearman Rho test. The results showed that respondents were predominantly aged 36–45 years (40.8%), predominantly female (53%), with the majority undergoing general surgery (49%), and having an ASA II health status (63%). In terms of education, the majority of respondents were high school graduates (67.1%), while the highest anxiety level was in the moderate category (83.7%). Spearman's Rho analysis yielded a p-value of 0.039 < 0.05, thus accepting the alternative hypothesis (Ha). Therefore, it can be concluded that there is a significant relationship between education level and preoperative patient anxiety during spinal anesthesia procedures. This finding confirms that increasing knowledge through education plays a significant role in reducing anxiety before medical procedures.